KEBUTUHAN PELATIHAN BAGI MANAJER MARKETING - Ratna Puspitasari (Perspektif Ilmu Pendidikan, 2009)
Considering that training is needed to improve the performance , this research aimed at identifying the training need for of marketing manager in PT Menara Indonesia by employing the competence model of Spencer and Spencer Based on its purpose and scope, this research is classified as a case study and qualitative research. The data was collected using Delphi technique and document study. Then the data were analysed by using Miles and Huberman’s metrhod consisting of thre steps: reduction, description, and description of the data. As the result of the study, this research idintified the training needs for marketing manger in PT Menara Inonesia among which are Team Leadership and Technical /Professional/ Managerial Expertise.